[Afisz. Incipit] In Token To The American Nation From The Schools Of Poland On The Occasion Of The 150th Anniversary Of The Independence Of The United States / Kaliszczak Z. - Kaliszczak, Zbigniew (1903-1985) ([wydawca nieznany], 1926)
Afisz z okazji 150-lecia niepodległośći USA.